KESALAHAN PENGGUNAAN RELATIVSATZ MAHASISWA PADA MATA KULIAH SCHREIBFERTIGKEIT I - Syamsurijal, Syamsurijal (Interference: Journal of Language, Literature, and Linguistics, 2020)
Abstract. The purpose of this study is to describe the mistakes made by the students in the use of Relativ Sentence. The method used in this study is descriptive qualitative. The data sources are students of Department of German Education, State University of Makassar. The data in this study are the sentences that contain elements Relativ Sentence from the essays made by the students. The instruments used are divided into two parts, the researcher as the primary instrument, and a table which serves as a supporting instrument. The results showed that there are still quite a lot of mistakes made use of Relativ Sentence in their essays, especially in terms of placement of the verb, in the case of the use Relativpronomen Nominativ, Akkusativ, and dative, as well as the errors in the position of relative clause. Based on the results of the study, it can be concluded that there are still many students of the German Language Study Program in 2019 who do not understand the Relativsatz material well.